KOMUNIKASI KELOMPOK VIRTUAL LEADER PEMASARAN ASURANSI - Miming Saputra Gunawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Globalization is a process of making something (object or behavior) a characteristic of every individual in this world without being limited by region. Globalization can also mean that several different characteristics (read: culture) can interact massively. The rapid development of the world of communication technology has brought tremendous benefits to the progress of human civilization. Communication activities that previously required such complicated equipment, have now been relatively replaced by automatic machines. Communication activities in terms of exchange or interaction between different cultures are inevitable in the current era of globalization. After the COVID-19 Pandemic, changes in the order of social life occur in general. The form of direct face-to-face communication is increasingly limited in the world of business, education, the world of daily interactions and others. One form of communication in the business world is Whatsapp Group. With the pandemic, communication via Whatsapp Groups is more intense. In the context of communication, one of which is the context of group communication. The form of group communication began to shift from face-to-face communication to virtual communication through social media or other platforms. Like it or not, all human activities are getting faster and faster. This paper tries to describe the virtual group communication activities that occurred in the Victory West Leaders whatsapp group in the era of the COVID-19 pandemic. The key factors in this virtual group activity are the common goals of the group, leadership factors from leaders and individual awareness of group members and the togetherness factor in time. The pandemic situation forced the activities of business groups to be more tightened through Whatsapp Group virtual communication activities. This aims to maintain the stability of team productivity. Keywords: Group Communication, Virtual Communication, Whatsapp Group, COVID -19, Insurance Marketing Leader